Vocational School Readiness for Batik Design Innovation: A Literature-Based Exploration of Challenges and Opportunities - Lulu Huda Arifin; Rina Febriana; Wesnina Wesnina (PT. Anagata Sembagi Education, 2025)
Batik design innovation plays a strategic role in sustaining Indonesia's cultural heritage while strengthening the creative industry sector. Vocational schools, as institutions responsible for preparing skilled creative workers, are expected to cultivate innovative competencies in batik design. However, varying levels of institutional readiness often hinder achieving these goals. This literature-based study aims to explore the preparedness of vocational schools to develop batik design innovation by mapping key challenges and opportunities revealed in previous studies. Using a narrative review approach, relevant journal articles, books, and policy documents were analysed through thematic categorisation encompassing curriculum, teacher competence, learning facilities, digital technology integration, and school industry collaboration. The findings indicate that vocational schools show potential to foster innovation but face significant challenges, including limited access to modern design technologies, outdated curricula, insufficient teacher expertise, and weak partnerships with the batik industry. Conversely, various opportunities emerge from increasing demand for creative batik products, government support for cultural education, and the growing availability of digital design tools that can enhance learning. This study highlights the need for comprehensive reforms in curriculum, professional development, and facility investment to strengthen innovation capacity in batik design education. The findings also offer practical insights for schools, policymakers, and industry partners to build an enabling ecosystem for batik design innovation collaboratively.